Multiple adaptations to polar and alpine environments within cyanobacteria: a phylogenomic and Bayesian approach - Chrismas, Nathan A. M.; Anesio, Alexandre M.; Sánchez-Baracaldo, Patricia (Frontiers in Microbiology, 2015)
Cyanobacteria are major primary producers in the polar and alpine regions contributing significantly to nitrogen and carbon cycles in the cryosphere. Recent advancements in environmental sequencing techniques have revealed great molecular diversity of microorganisms in cold environments. However, there are no comprehensive phylogenetic analyses including the entire known diversity of cyanobacteria from these extreme environments. We present here a global phylogenetic analysis of cyanobacteria including an extensive dataset comprised of available SSU rRNA gene sequences of cyanobacteria from polar and high altitude environments. Furthermore, we used a large-scale multi-gene (135 proteins and two ribosomal RNAs) genome constraint including 57 cyanobacterial genomes. Our analyses produced the first phylogeny of cold cyanobacteria exhibiting robust deep branching relationships implementing a phylogenomic approach. We recovered several clades common to Arctic, Antarctic and alpine sites suggesting that the traits necessary for survival in the cold have been acquired by a range of different mechanisms in all major cyanobacteria lineages. Bayesian ancestral state reconstruction revealed that twenty clades each have common ancestors with high probabilities of being capable of surviving in cold environments.